SF Cake House / Daniatay Donih ... [et al.] - Donih, Daniatay; Justin, Marsina; James, James; Boden, Reacle McAlister; Samdin, Nurul Izati Nadia (2014)
The business that we operated is name as SF Cake House. Our company is a partnership business, where we provided services and make product. Our company provided service such as bake cake class and product that we make is cakes that many kind of flavor. In our business, there are four important department sections where each of the section is handled by one manager who is also the partner of the business. Each department is help the company to run the company smoothly, the department are, administration department, marketing department, operational department, and financial department, the entire department are under the general manager. Our premise is located at K.K Plaza Second Floor, Kota Kinabalu. We choose this located, because the K.K Plaza is the place that many people will go to shopping and from that we can attract the customer to buy our product.